Vascular Endothelial-Targeted Therapy Combined with Cytotoxic Chemotherapy Induces Inflammatory Intratumoral Infiltrates and Inhibits Tumor Relapses after Surgery - Judy, Brendan F (Neoplasia Press Inc., 2012)
Surgery is the most effective therapy for cancer in the United States, but disease still recurs in more than 40% of patients within 5 years after resection. Chemotherapy is given postoperatively to prevent relapses; however, this approach has had marginal success. After surgery, recurrent tumors depend on rapid neovascular proliferation to deliver nutrients and oxygen. Phosphatidylserine (PS) is exposed on the vascular endothelial cells in the tumor microenvironment but is notably absent on blood vessels in normal tissues. Thus, PS is an attractive target for cancer therapy after surgery. Syngeneic mice bearing TC1 lung cancer tumors were treated with mch1N11 (a novel mouse chimeric monoclonal antibody that targets PS), cisplatin (cis), or combination after surgery. Tumor relapses and disease progression were decreased 90% by combination therapy compared with a 50% response rate for cis alone (P = .02). Mice receiving postoperative mch1N11 had no wound-related complications or added systemic toxicity in comparison to control animals. Mechanistic studies demonstrated that the effects of mch1N11 were associated with a dense infiltration of inflammatory cells, particularly granulocytes. This strategy was independent of the adaptive immune system. Together, these data suggest that vascular-targeted strategies directed against exposed PS may be a powerful adjunct to postoperative chemotherapy in preventing relapses after cancer surgery.